Simulação da trajetória de partículas sólidas em peneiras através do método dos elementos discretos - Silveira, Jeniffer Cristina (2017)
The mixture formed by drilling fluid and gravels returning from the oil well characterizes the residue from the well drilling operation. For the proper disposal of this residue a solid control system is necessary in drilling probes, in order to remove solids from the mixture. In contrast, the maximum possible recovery of the fluid is obtained. Vibrating screens are the first equipment of the solids separation system. They are designed to process all surrounding volume of the blend. It is characterized by the separation of coarse solids, preventing the passage of material with a size larger than the aperture of the screen. The characteristics and particularities of the sifting operation make the modeling of this process challenging. In this dissertation the gravel sieving is modeled using the method of discrete elements (DEM). The method counts the influence of different factors on the dynamics of each particle. The gravel is represented by the approximation with spherical particles. The material used to describe the particles was the marble, rock composed of the main minerals found in drilling gravels of national soils (calcite, quartz and dolomite). The sieve basket is described by particles of infinite mass and radius and the screen is modeled as a perforated contour. DEM accounts for the forces acting on the particles decomposed into normal and tangential components. To describe the force due to the contact was used the Hertz nonlinear model for the normal component and the Lee and Herrmann linear model for the tangential component. The simulated results consider the particle size distribution, the sieve inclination and the vibration direction angle and represent the behavior of the solid with a good approximation, which may aid in the improvement of the sieve design and optimization of the operation.